Anthropologie à Dieu? Nizäa und seine Inspiration für den Umgang mit Herausforderungen für die christliche Erzählung vom Menschen - Schärtl, Thomas (Münchener theologische Zeitschrift, 2025)
Transhumanism, posthumanism and many visions that accompany the discussions of artificial intelligence pose challenges to the Christian narrative of being human. Classical anthropocentrism no longer seems to be able to provide an adequate answer to these challenges. The article advocates a so-called 'anthropology of relation' that is inspired by the dogmatic decisions of the Council of Nicaea: To be human means to be capable of an 'intimate' encounter with God. This encounter presupposes a certain disposition: namely a special way of empathy and a second-person perspective. Because this characteristic is not to be understood in an exclusivist way, the present article advocates the somewhat provocative hypothesis that, for instance, technologically embodied robot intelligences or complete ecosystems can also stand in their own, perhaps differently accentuated relationships to God.